EFFECT OF BOATTAIL GEOMETRY ON FLOW STRUCTURE AND DRAG OF AXISYMMETRIC BODY - Hùng (Journal of Military Science and Technology, 2021)
This study presents effect of boattail model on flow behavior and drag of axisymmetric model at low-speed conditions. Boattail geometry with different length and angle was investigated by numerical approach. This study uses Reynolds-averaged Navier-Stokes equations with turbulent model k- ω. The numerical process was conducted at Le Quy Don Technical University. Numerical results showed that boattail geometry strongly affects drag of the model. At high boattail angle, separation flow occurs on the surface and increases drag of the model. Distributions of velocity, pressure, skin friction on the boattail surface were investigated and presented in details in this study.